Tort Liability of Public Authorities in Light of the Legal Doctrine of Stanislaw Kasznica's Era and Contemporary Doctrine: The Remarks of a Civil Law Specialist (Contemporary Central & East European Law, 2024)
The author of the text notes that the development of administrative law and its science at the turn of the 19th and 20th centuries was related to the development of the law on tort liability of public authorities. This is most evident in the example of French law. It is one of the few cases where the science of administrative law and administrative court judgments contributed to the development of civil law and its science. It is about the issues of tort liability of legal persons characterized by an extensive organizational structure. Therefore, it makes sense to analyze the issue of tort liability of public authorities in connection with the analysis of the scientific achievements of Stanisław Kasznica, an outstanding Polish specialist in administrative law. The author claims that the publications of Stanisław Kasznica, especially his textbook Polish Administrative Law, first edition 1943). influenced the development of both Polish administrative law and the law on tort liability of public authorities. In particular, i.a. under the influence of this author’s position, the opinion that the tort liability of public authorities is of a civil law and not administrative law nature has become established in Poland. The author of the text tries to show that the issue of tort liability of public authorities generates legal problems in every epoch. The problems that exist today differ from those that existed in the times of Stanisław Kasznica. Concluding his arguments, the author puts forward the thesis that the issue of tort liability of public authorities tends to elude the standards of classical civil law. Therefore, these issues should be dealt with by both civil and administrative law specialists.